2015
DOI: 10.1371/journal.pone.0124865
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein-3 Increases Triple-Negative Breast Cancer Cell Invasiveness via Induction of Metalloproteinase Expression

Abstract: It has been recently found that metallothionein-3 (MT3) enhances the invasiveness and tumorigenesis of prostate cancer cells. This finding is in contrast to those of earlier studies, which indicated that overexpression of MT3 in breast cancer and prostate cancer cell lines inhibits their growth in vitro. Therefore, to clarify the role of MT3 in breast cancer progression, we analyzed the effect of MT3-overexpression on proliferation, invasiveness, migration, and tumorigenesis of breast cancer MDA-MB-231/BO2 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…For example, Wu et al reported that MT1E, one of the metallothioneins, was considered to be important in bladder cancer cell migration and tumour stage [53]. It has been demonstrated that metallthionein-3 induces migration, proliferation, and invasion in triplenegative breast cancer cells via the induction of metalloproteinase expression [54]. Another key molecular mediator of DC-SIGNR in colon cancer cells is MMP9.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Wu et al reported that MT1E, one of the metallothioneins, was considered to be important in bladder cancer cell migration and tumour stage [53]. It has been demonstrated that metallthionein-3 induces migration, proliferation, and invasion in triplenegative breast cancer cells via the induction of metalloproteinase expression [54]. Another key molecular mediator of DC-SIGNR in colon cancer cells is MMP9.…”
Section: Discussionmentioning
confidence: 99%
“…TIMP-3 is TIMP family member that displays unique molecular properties and features. For example, TIMP-3 appears able to induce apoptosis in melanoma cells, retinal pigment epithelial cells, and breast cancer cells [ 26 28 ]. TIMP-3 also acts as a local cytokine in bone, regulating bone metabolism by suppressing osteoblast differentiation and inducing osteoblast apoptosis [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…AOX1 hydroxylates heterocycles and oxidizes various aldehydes and participates in a myriad of cellular activities (Terao et al, 2006). GPX1 and SOD3 encode for antioxidant enzymes (Guo et al, 2003), while MT3 is known to enhance invasiveness and tumorigenesis (Kmiecik et al, 2015). Gg likely exhibits pro-oxidant actions in MCF-7 cells via downregulation of AOX-1, GPX1 and SOD3.…”
Section: Glaucarubulone Glucoside Induces Pro-oxidant Activity In Canmentioning
confidence: 99%